Serum vitamin D and diabetic foot complications. Issue 1 (1st January 2019) - Greenhagen, Robert M.; Frykberg, Robert G.; Wukich, Dane K.
ABSTRACT: Background : Foot complications such as ulceration and neuropathy are common complications of diabetes mellitus (DM). Previous reports have demonstrated a possible increased risk of these complications in diabetic patients with low levels of serum vitamin D.Objectctive : The purpose of this study is to compare serum vitamin D levels in diabetic patients with and without Charcot neuroarthropathy (CN), peripheral arterial disease (PAD), infection (DFI), ulceration (DFU), and peripheral neuropathy (DPN). Design : A retrospective chart review of all patients undergoing foot and ankle surgery with a history of DM over a 13 month period was performed. From this cohort, fifty subjects with CN were matched with 50 without CN and preoperative lab values were compared. A secondary evaluation was performed on the subjects' other comorbidities including PAD, DFI, DFU, and DPN. Results : Seventy-eight percent of our patients had vitamin D deficiency or insufficiency. Preoperative serum vitamin D levels were not significantly different between diabetic patients with and without CN (p = 0.55). Diabetic patients with PAD (p = 0.03), DFI (p = 0.0006), and DFU (p = 0.04) were all found to have significantly lower serum vitamin D levels than diabetic patients without these complications. Lower levels of serum albumin and higher serum creatinine were also noted with subjects with PAD, DFI, DPN, and DFU. While seasonal serum vitamin D level fluctuation was noted, this difference did not reach statistical significance with the numbers available. Conclusion : We found various lower extremity complications to be associated with low serum vitamin D including PAD, DFI, and DFU. While other studies have questioned the role of vitamin D and CN, we were unable to identify any significant difference between diabetic patients with and without Charcot neuroarthropathy. Level of evidence : Level 2